Positive Virological Outcomes of HIV-Infected Patients on Protease Inhibitor-Based Second-Line Regimen in Cambodia: The ANRS 12276 2PICAM Study - Olivier Ségéral; Olivier Ségéral; Eric Nerrienet; Eric Nerrienet; Sansothy Neth; Bruno Spire; Vohith Khol; Laurent Ferradini; Saramony Sarun; Chandara Mom; Sopheak Ngin; Charlotte Charpentier; et al. (Frontiers in Public Health, 2018)
BackgroundAssessment of virological outcomes among HIV-infected patients receiving protease (PR) inhibitor-based second-line regimen are uncommon in Cambodia. The objective of this study is to assess the virological effectiveness of this regimen as well as impact of adherence boosting for patients experiencing virological failure.MethodsThe 2PICAM study (Clinicaltrial: NCT01801618) is a cross-sectional study of HIV-infected adults on PR inhibitor-based second-line regimen since at least 6 months, conducted in 13 representative sites, comprising more than 90% of the target population. Adults with HIV RNA above 250 copies/mL (threshold of the assay) at inclusion received boosted adherence counseling during 3 months followed by HIV RNA control. For confirmed virological failure, genotype resistance test was performed and expert committee used results for therapeutic decision.ResultsAmong the 1,317 adults enrolled, the median duration of second-line regimen was 5 years. At inclusion, 1,182 (89.7%) patients achieved virological success (<250 copies/mL) and 135 (10.3%) experienced a virological failure (>250 copies/mL). In multivariable analysis, factors associated with virological success were: CD4 cell count between 201 and 350/mm3 (OR: 4.66, 95% CI: 2.57–8.47, p < 0.0001) and >350/mm3 (OR: 6.67, 95% CI: 4.02–11.06, p < 0.0001), duration of PI-based regimen >2 years (OR: 1.64, 95% CI: 1.03–2.62, p = 0.037), ATV-containing regimen (0R: 1.65, 95% CI: 1.04–2.63, p = 0.034) and high level of adherence (OR: 2.41, 95% CI: 1.07–5.41, p = 0.033). After adherence counseling, 63 (46.7%) patients were rescued while 72 (53.3%) were not. For the 54 patients with genotype resistance tests available, high or intermediate levels of resistance to lopinavir, atazanavir, and darunavir were reported for 13 (24%), 12 (22.2%), and 2 (3.7%) patients, respectively. Change to an alternative PR inhibitor-based regimen was recommended for 17 patients and to third-line regimen, including integrase inhibitors for 12.ConclusionThis study reports high rate of virological suppression of second-line regimen and importance of adherence boosting prior to deciding any change of ART regimen. Genotype resistance tests appear necessary to guide decisions. Such information was of great importance for National HIV Program to adapt guidelines and program needs for third-line regimen.